2020
DOI: 10.4067/s0717-95022020000200305
|View full text |Cite
|
Sign up to set email alerts
|

Brain Structure Morphology After Being Fixated With Ethanol on Electron Microscope

Abstract: Fixation is one of the processes in preparing histology and pathology. The common material for fixation is buffered formalin including paraformaldehyde. However, the effect of the damaged cells, which is fixed for a long time, causes the research for other fixation materials to become necessary. In addition, paraformaldehyde is also harmful to human body and natural environment. Ethanol is one of the alternative fixation materials, which has been used for two hundred years. It has been used for many purposes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Research conducted by Arni et al states that alcohol fixation can be done with ethanol with gradual concentrations, from 40% for 24 hours and up to 60% within the next 24 hours. The results of this study showed a good contour cell seen in the light microscope [11].…”
Section: A Confocal Imaging Of Cle During Operation B Convivo Ex Vivo...supporting
confidence: 56%
See 1 more Smart Citation
“…Research conducted by Arni et al states that alcohol fixation can be done with ethanol with gradual concentrations, from 40% for 24 hours and up to 60% within the next 24 hours. The results of this study showed a good contour cell seen in the light microscope [11].…”
Section: A Confocal Imaging Of Cle During Operation B Convivo Ex Vivo...supporting
confidence: 56%
“…NBF 10% or FFPE is used routinely for specimens viewed under the light microscope. Meanwhile, glutaraldehyde, or a mixture of formaldehyde and glutaraldehyde and osmium tetraoxide is used routinely for specimens viewed under an electron microscope [3,11]. Alcohol can also be used for fixation, but it is necessary to pay attention to its percentage and fixation time.…”
Section: A Confocal Imaging Of Cle During Operation B Convivo Ex Vivo...mentioning
confidence: 99%